Key Aspects to Consider about Beneficial and Harmful Effects on the Central Nervous System by the Endocannabinoid Modulation Linked to New Cardiovascular Therapies - Martín Giménez, Virna Margarita (2019)
The endocannabinoid system (ECS) is closely related to the central nervous system (CNS) and exerts a promising therapeutic potential on the cardiovascular system, mainly through its neuromodulatory, neuroprotective, and neuroinflammatory effects. For this reason, when designing new treatments for different cardiovascular pathologies, it is necessary to consider the side effects that such therapies can cause at the neurological level. ObjectiveTo deepens the knowledge of each cannabinoid (CB) and the molecular mechanisms that can lead to undesired results to analyze its possible use in cardiovascular therapy.MethodsThe present review analyzes the psychoactive consequences of anandamide and other similar substances such as other endocannabinoids, phytocannabinoids, and synthetic cannabinoids, to assess their little-explored therapeutic potential in clinical investigations. Finally, the major behavioral tests most used until the moment to predict possible changes in the conduct of animals treated with various substances of cannabinoid nature are summarized. It has been observed that endocannabinoids have few adverse central nervous effects, unlike the phytocannabinoids, synthetic cannabinoids and antagonists of CB receptors. These molecules act on typical receptors due to a similar spatial configuration; however, their structure is not identical between them. For this reason, the competition and displacement of endogenous ligands of the ECS by exogenous cannabinoids provokes an alteration in the CNS normal functioning, leading to the associated side effects. An exhaustive analysis of each cannabinoid and the molecular mechanisms that can lead to undesired results is necessary at the time of proposing them as news cardiovascular therapeutic alternatives.